2015
DOI: 10.4149/bll_2015_041
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio in inflammatory bowel disease – As a new predictor of disease severity

Abstract: Background: The aims of this study were to investigate the utility of neutrophil-to-lymphocyte ratio (NLR) as a simple and readily available predictor for clinical disease activity in infl ammatory bowel disease (IBD). Methods: Sixty-six patients (22 CD, 44 UC) and 41 healthy controls were enrolled in the study. Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) levels and complete blood count (CBC) were measured. The neutrophil and lymphocyte counts were recorded and NLR was calculated. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 24 publications
6
70
0
2
Order By: Relevance
“…Alternatively, total WCC and platelet count have been advocated as indicators of severity of appendicitis, but with varying success [22] . Evidence to date demonstrates that NLR is a good marker of subclinical inflammation, with studies showing that it correlates with the severity of acute inflammatory bowel disease and acute cholecystitis [10,12,13] . Additionally, recent studies have observed that NLR correlates with colorectal cancer stage and oncological outcome and is currently being considered as a biomarker [15,16] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, total WCC and platelet count have been advocated as indicators of severity of appendicitis, but with varying success [22] . Evidence to date demonstrates that NLR is a good marker of subclinical inflammation, with studies showing that it correlates with the severity of acute inflammatory bowel disease and acute cholecystitis [10,12,13] . Additionally, recent studies have observed that NLR correlates with colorectal cancer stage and oncological outcome and is currently being considered as a biomarker [15,16] .…”
Section: Discussionmentioning
confidence: 99%
“…The use of simple inexpensive biomarkers could further substantially reduce negative appendicectomy rates, while ensuring that severe appendicitis cases are treated expeditiously. Although the mortality for perforated appendicitis is low, the morbidity can be high, and therefore, surgery remains the gold standard for severe appendicitis (phlegmonous or gangrenous) [11][12][13][14][15][16][17][18][19][20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…assessed NLR and CRP levels using the Harvey-Bradshaw index and the Truelove and Witts criteria, by matching 22 CD and 44 UC patients with active and inactive disease with 41 healthy controls [26]. The authors found that the mean NLR value was 5.25 in CD patients with active disease in contrast to 1.68 in the healthy control group and 1.78 in patients with inactive CD.…”
Section: Discussionmentioning
confidence: 99%